Information, amplification and financial crisis - Toni Ahnert; Ali Kakhbod (Bank of Canada, 2014)
We propose a parsimonious model of information choice in a global coordination game of regime change that is used to analyze debt crises, bank runs or currency attacks. A change in the publicly available information alters the uncertainty about the behavior of other investors. Greater strategic uncertainty makes private information more valuable, so more investors acquire information. This change in the proportion of informed investors amplifies the impact of the initial change in public information on the probability of a crisis. Our amplification result explains how a small deterioration in public information can cause a financial crisis. – – Les auteurs proposent un modèle parcimonieux du choix de l'information dans le cadre d'un jeu global de coordination autour d'un changement de régime – jeu utilisé pour analyser les crises d'endettement, les retraits massifs de dépôts bancaires ou les attaques contre la monnaie. Toute modification de l'information rendue publique fait varier l'incertitude associée au comportement des autres investisseurs. Plus l'incertitude stratégique grandit, plus l'information privée est prisée, et donc plus les investisseurs acquièrent de l'information. Cette évolution de la proportion d'investisseurs avertis amplifie les effets que produit la modification de l'information publique sur la probabilité d'une crise. Grâce à cette amplification, les auteurs parviennent à expliquer comment une légère aggravation dans les données à disposition peut engendrer une crise financière.
Keywords: D83; G01; 330; Financial institutions; Financial stability